Semantic web technologies in information architecture - Coneglian, Caio Saraiva [UNESP]; Roa-Martinez, Sandra Milena [UNESP]; Da Costa Ferreira, Ana Maria Jensen Ferreira [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio; Segundo, José Eduardo Santarem [UNESP] (Universidad de Antioquia, 2019)
The researches of Information Architecture and Semantic Web are increasingly necessary, due to the need to have an understanding of the context of the information, both from the perspective of human users and non-humans/machines users. These two study fields contribute to improving the way informational content is presented and used in digital environments. Thus, this paper identified and analyzed the relationships between Information Architecture systems and Semantic Web resources, presenting how each Information Architecture system can benefit from the incorporation of Semantic Web technologies. For this, a qualitative methodology was used, with a descriptive and exploratory approach, relating the five systems of Information Architecture with the concepts, technologies and applications of the Semantic Web. As results, it was possible to verify that all systems of Information Architecture can be enriched with Semantic Web technologies. In this way, it was concluded that the application of Semantic Web technologies in Information Architecture systems contributes to a semantic structure of digital information environments.
Tecnologias da web semântica na arquitetura da informação
Keywords: Digital information environments; Information architecture; Information architecture systems; Semantic web; Semantic web concepts; Technologies